A Survey on Wireless Sensor Networks and Their Applications - Brindha, G.; Thanigaivelu, K. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Wireless sensor network is emerging field because of its wide applications. It is a wireless network which subsist a group of small sensor nodes which communicate through radio interface. These sensor nodes are composed of sensing, computation, communication and power as four basic elements. Many routing, power management, and data dissemination protocols have been specifically designed for WSNs where energy awareness is an essential design issue. But limited energy, communication capability, storage and bandwidth are the main resource constraints. The network should have selforganizing capabilities as the positions of individual nodes are not predetermined. The flexibility, fault tolerance, high sensing fidelity, low cost, and rapid deployment characteristics of sensor networks create many new and exciting application areas for remote sensing. Our survey is based on various aspects of wireless sensor networks. In this paper we also discussed various types of WSNs and their applications